FEATURES OF THE SYSTEM OF INTERRELATIONSHIPS AND THE FEELINGS OF EMPATHY IN ELEMENTARY STUDENTS (American Journal of Pedagogical and Educational Research, 2025)
This article presents theoretical information about the most important social feelings of empathy, the important role of empathy in the formation of a child's personality and in his life in general, and at the same time, with the help of empathy, the child learns to understand other people, their inner experiences, learns to understand and help the dignity of another person.